Strategi Peningkatan Kepuasan Pasien Dan Kualitas Pelayanan Di Rumah Sakit Dalam Perspektif Tinjauan Teoritis - Rocky Fransiskus Budiman; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
The hospital also has the main task of providing complete individual health services with efforts to heal, recover, improve, prevent, referral services, research and development and community service. The purpose of writing this scientific article is to find out and review theoretically from various literature and strategies to improve patient satisfaction and quality of service in hospitals. The method used is a theoretical study by analyzing and comparing existing theories. The results of this theoretical study, namely the strategies carried out by increasing human resources, the speed of staff response, and satisfaction can be identified by comparing the expectations and experiences of the performance of health service providers. By doing this strategy can provide a desire of patient hope. It was concluded that strategies to increase patient satisfaction and health quality can realize patient expectations arising from the actions of health workers as the performance of health services and during a good treatment process. In the strategy carried out the patient will evaluate and assess the product or service quality that has been received. Hospital agencies also need to improve service quality strategies to realize patient expectations. Patient satisfaction in assessing quality or good service, and is an important measurement that is fundamental to the quality of service. This is also because by providing information on the success of quality service providers, the values ​​and expectations of patients will increase.